Effects of perceptions of care, medical advice, and hospital quality on patient satisfaction after primary total knee replacement: A cross-sectional study. - Tom Schaal; Tonio Schoenfelder; Joerg Klewer; Joachim Kugler (PLoS ONE, 2017)
Introduction The increase in the number of patients presenting with osteoarthritis in the past decade has led to a 32% increase in knee replacement surgeries designed to reduce restrictions on patient movement and improve their quality of life. Patient satisfaction is becoming an increasingly important indicator of quality of care. This study was designed to identify predictors of various service components in the treatment process and hospital key performance indicators significantly associated with patient satisfaction. Materials and methods A multicenter cross-sectional study was conducted with 856 patients having their primary total knee replacements at 41 hospitals. Patient satisfaction was queried via a validated, multidimensional questionnaire mainly using a six-point scale. In addition to bivariate calculations, patient satisfaction was the dependent variable in a binary logistic regression model. Results The bivariate analysis showed a strong association between satisfaction and sex (male or female), the patients' health before admission, and the length of stay. The number of cases treated at each hospital did not reveal any impact on satisfaction. The multivariate analysis identified three predictors associated with overall satisfaction. The strongest factor was the treatment outcome and the weakest was the quality of food. It became apparent that the statutory procedure minimums were not being met. Conclusions The relevant factors influencing patient satisfaction were partially the same as previous study results and allowed more detailed conclusions. The results provide suggestions across hospitals that could help health care providers better meet needs of patients after knee arthroplasties.